Social Support for the Quality of Life of Pulmonary Tuberculosis Patients - Keristina Ajul; Lilik Pranata (SAINTIS Publishing, 2025)
Pulmonary tuberculosis is an infectious disease that can affect the quality of life of sufferers. Social support is often considered a contributing factor to the quality of life of pulmonary TB patients, but research results on this relationship are still mixed. This study aims to analyze the relationship between social support and the quality of life of pulmonary TB patients. This study used a quantitative design with a cross-sectional approach. consisting of 33 pulmonary TB patients registered at one of the health centers in Palembang city. Data were collected using a questionnaire that included a social support scale, a stigma scale, and the WHOQOL-BREF instrument to measure quality of life. Correlation analysis showed that social support had a weak positive relationship with quality of life (r = 0.33; p = 0.05) which means that the higher the social support received by the respondents, the better their quality of life. Social support contributes positively to improving the quality of life of pulmonary tuberculosis patients